APPROACHES TO DEFINING ESSENCE OF CONTROL IN PUBLIC ADMINISTRATION THEORY - Shevchenko O.M. (Pressing Problems of Public Administration, 2017)
The concept of control in the theory of management is considered as a phenomenon, functions,process, and system. The origins of the term emergence are described, and the analysis of thework of scientists involved in a study of its content is conducted. Based on the analysis, a scheme ofthe control system is built. The concept of state financial control as a financial control variety and anarrower level of control are analyzed.